Human capital and the FDI-Income inequality nexus in African countries: Panel smooth transition regression approach - Kouassi YEBOUA (Theoretical and Applied Economics, 2019)

(untitled)
The link between foreign direct investment (FDI) and income inequality has received little attention in the literature. This paper investigates empirically the relationship between FDI and income inequality using an unbalanced panel data made up of 26 African countries over the period 1990-2013. First, we estimate the linear relation using the now popular System-GMM estimation techniques to control for potential endogeneity bias. We find that FDI deepens income inequality. Secondly, we go further in the analysis to examine whether the impact of FDI on income inequality depends on absorptive capacity, by employing a panel smooth transition regression model which is more suitable to deal with cross-country heterogeneity issues. We use human capital stock as a proxy for absorptive capacity, and the results show that the impact of FDI on income inequality is conditioned by the level of human capital stock in the host country. Specifically, we find that FDI increases income inequality in countries with low levels of human capital stock, and reduces income inequality in countries with high levels of human capital stock. These findings suggest that policies oriented towards FDI liberalization in African countries should go hand in hand with policies that aim at improving human capital stock in order to mitigate the potential inequality-increasing effect of FDI.